2013
DOI: 10.3389/fncel.2013.00170
|View full text |Cite
|
Sign up to set email alerts
|

Increased physical activity is not enough to recover astrocytic population from dark-rearing. Synergy with multisensory enrichment is required

Abstract: Elimination of sensory inputs (deprivation) modifies the properties of the sensory cortex and serves as a model for studying plasticity during postnatal development. Many studies on the effects of deprivation have been performed in the visual cortex using dark-rearing as a visual deprivation model. It induces changes in all cellular and molecular components, including astrocytes, which play an important role in the development, maintenance, and plasticity of the cortex, mediated by cytokines which have been te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…The effect of environment can be dramatic; for example, dark-reared animals in standard cages show a striking reduction in the number of astrocytes compared to controls. In contrast, dark-reared animals in enriched cages have more astrocytes than control animals (Bengoetxea et al 2013). These results suggest that even the basic neuroanatomical consequences of dark rearing can be very different when animals must learn to solve tasks like navigation and food finding using their remaining senses.…”
Section: Blindness Occurs At Many Stages Of Developmentmentioning
confidence: 91%
“…The effect of environment can be dramatic; for example, dark-reared animals in standard cages show a striking reduction in the number of astrocytes compared to controls. In contrast, dark-reared animals in enriched cages have more astrocytes than control animals (Bengoetxea et al 2013). These results suggest that even the basic neuroanatomical consequences of dark rearing can be very different when animals must learn to solve tasks like navigation and food finding using their remaining senses.…”
Section: Blindness Occurs At Many Stages Of Developmentmentioning
confidence: 91%
“…The beneficial effect of physical exercise may, in part, be attributed to upregulated neurotrophins, which would help to protect neural functions (Hillman et al, 2008 ). In addition to these effects on neurons, recent studies have demonstrated that physical exercise induces structural and biochemical changes in astrocytes as well as in neurons (de Senna et al, 2011 ; Bengoetxea et al, 2013 ). These studies suggested that the Olig2-lineage astrocytes in the GP can be a good model to delineate the relationship between neuronal activities and astrocytic morphologies.…”
Section: Introductionmentioning
confidence: 99%
“…At P48, half of the rats were kept in Zürich (low-altitude group), and the other half transported to the Jungfraujoch High Altitude Research Station on the Jungfraujoch (JFJ, 3450 m asl), (high-altitude group) in a single journey of 250 min duration. Both low- and high-altitude groups were then housed at 22°C room temperature with a 12 h light/dark cycle and access to food and water ad libitum , either in standard laboratory conditions (SC) or in an enriched environment that included voluntary exercise (EE) (Bengoetxea et al, 2013), and received either sucrose, (EE + veh), or the tyrosine kinase inhibitor Vandetanib (EE + inh).…”
Section: Methodsmentioning
confidence: 99%